Fifteen-minute consultation: A structured approach to the assessment of a child with earache. Issue 1 (27th September 2021) - Halliday, Edwin; Wooles, Nicola; Grainger, Joe
Abstract : Earache, or otalgia, in children is common. Diagnosis can be challenging due to the range of causes. Assessment involves a thorough history and examination. Identification of associated otological symptoms, including discharge, hearing loss, vertigo and facial nerve weakness, is helpful and can aid diagnosis. Examination should involve looking at the external ear, otoscopy to assess the ear canal and tympanic membrane and documentation of facial nerve function. If otological examination is normal, further examination looking for non-otological causes may be guided by the history. Investigations are often unnecessary but may include blood tests, audiology and imaging. Most otalgia is caused by an acute infection, which is self-limiting and can be managed in the community. However, ear, nose and throat (ENT) advice and input may be required for systemically unwell children or those who fail to improve despite appropriate medical therapy.